Professional Reintegration after Pelvic and Acetabular Trauma - Muhammad Zoha Farooq, Faheem Ahmed, Affan Tayyab, Muhammad Gulfam Shahzad, Dileep Kumar, Malik Naveed Iqbal, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Pelvic ring and acetabulum injuries are complex injuries varying in severity and complications resulting in serious morbidity in surviving individuals which as a result can be a major contributor to reintegration of patients in professional services. Therefore its important to evaluate to what extent affected patients can return to pre injury work status and how their quality of life is affected. The objective of this study is to evaluate reintegration of affected patients in profession in a two year follow up after acetabular and pelvic ring injuries Material and Methods: Using local Trauma Registry of Orthopedic Trauma department in Shaheed Mohtarma Benazir Bhutto Institute of Trauma (SMBBIT) a retrospective Cohort study was conducted. All patients between age 18 to 60 who had a Acetabulum or Pelvic Ring fracture presented in SMBBIT during July 2017 to July 2019 and were treated by Orthopedic Trauma department were included in study. Multivariate logistic regression analysis was used to model reintegration to profession. Affected patients were classified as “Reintegrated to profession” if they have earned a month salary after 13 to 24 months rehabilitation post treatment. For unemployed patients along with majority of women who were domestic home makers, reciprocate basic household chores to pre injury injury level were classified as “ Reintegrated “ Fracture classification, Age, Gender, Fracture of Spine , Nerve Injuries of Lumbo Sacral Spine and/or lower limb and work status before injury were considered prognostic covarities. Results: Almost 70 percent of 180 researched patients were classified reintegrated. This means a reduction of 20 percent in employment for Pelvic ring injuries and 10 percent reduction in employment for acetabular fractures post treatment. Employment status before injury was the main predictor for reintegration. Older patients had a less chance to return to work in comparison to young individuals. Patients with Nerve injuries and fracture of spine had almost 80 percent higher risk for not being reintegrated. Conclusion: Acetabular fractures and Pelvic ring injuries currently lead to greater loss of reintegration to profession or domestic work. Trauma to Pelvis and Acetabulum threatens the social security of patients. Therefor rehabilitation and follow up care should be optimized to reduce post traumatic disability and reduce the economic burden of work disability.